Front Cover: Soyasaponin A2 Alleviates Steatohepatitis Possibly through Regulating Bile Acids and Gut Microbiota in the Methionine and Choline‐Deficient (MCD) Diet‐induced Nonalcoholic Steatohepatitis (NASH) Mice. Issue 14 (21st July 2021) - Xiong, Fei; Zheng, Zhongdaixi; Xiao, Lingyu; Su, Chuhong; Chen, Junbin; Gu, Xiangfu; Tang, Jiaqi; Zhao, Yue; Luo, Huiyu; Zha, Longying
Abstract : Mol. Nutr. Food Res . 2021, 65, 2100067 DOI: 10.1002/mnfr.202100067 Soyasaponin A2 alleviates steatohepatitis by modulating the gut microbiota composition, altering the bile acids profiles in liver and serum, and increasing the ileum expression of Farnesoid X receptor (FXR) and fibroblast growth factor (FGF‐15) in the methionine and choline deficient diet‐induced non‐alcoholic steatohepatitis (NASH) mice. This is reported by Longying Zha and co‐workers in article number 2100067 .